Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 28200 by abdo imad last updated on 21/Jan/18

let give I= ∫_0 ^1   ((ln(1+x))/(1+x^2 ))dx  and J=∫∫_([0,1]^2 )    (x/((1+x^2 )(1+xy)))dxdy  calculate J by two methods then find the value of I.

letgiveI=01ln(1+x)1+x2dxandJ=[0,1]2x(1+x2)(1+xy)dxdycalculateJbytwomethodsthenfindthevalueofI.

Commented by abdo imad last updated on 22/Jan/18

we have  J= ∫_0 ^1 (∫_0 ^1    (x/(1+xy))dy)(dx/(1+x^2 )) but  ∫_0 ^1   (x/(1+xy))dy= [ln(1+xy)]_(y=0) ^(y=1) =ln (1+x) so  J= ∫_0 ^1    ((ln(1+x))/(1+x^2 ))dx   from another side  J= ∫_0 ^1  ( ∫_0 ^1      (x/((1+x^2 )(1+xy)))dx)dy let decompose  F(x)=  (x/((1+x^2 )(1+xy)))=   (α/(1+xy))+  ((ax+b)/(1+x^2 ))  α= lim_(x→((−1)/y))  (1+xy)F(x)=   ((−1)/(y( 1+(1/y^2 ))))= ((−1)/(y+(1/y)))= ((−y)/(1+y^2 ))  lim_(x→+∝) xF(x)=0= (α/y) +a ⇒a= −(α/y) =  (1/(1+y^2 ))  F(x)=  ((−y)/((1+y^2 )(1+xy))) +  (((1/(1+y^2 ))x +b)/(1+x^2 ))  F(0)=0 = ((−y)/(1+y^2 )) +b⇒ b=(y/(1+y^2 ))  and  F(x)= ((−y)/((1+y^2 )(1+xy))) + (1/(1+y^2 ()) ((x+y)/(1+x^2 )))  ∫_0 ^1 F(x)dx= ((−1)/(1+y^2 )) ∫_0 ^1   ((ydx)/(1+xy))  +(1/(2(1+y^2 ))) ∫_0 ^1   ((2x)/(1+x^2 ))dx +(y/(1+y^2 ))∫_0 ^1 (dx/(1+x^2 ))  = ((−1)/(1+y^2 )) [ln(1+xy)]_(x=0) ^(x=1)    +(1/(2(1+y^2 ))) [ln(1+x^2 )]_0 ^1   +(π/4) (y/(1+y^2 ))  −((ln(1+y))/(1+y^2 ))   +((ln2)/(2(1+y^2 )))  + ((πy)/(4(1+y^2 )))  J=−∫_0 ^1 ((ln(1+y))/(1+y^2 ))dy  +((ln2)/2) ∫_0 ^1   (dy/(1+y^2 ))  +(π/8) ∫_0 ^1  ((2ydy)/(1+y^2 ))  2J= (π/8)ln2  +(π/8) ln2= (π/4)ln2 ⇒J= (π/8)ln2  .

wehaveJ=01(01x1+xydy)dx1+x2but01x1+xydy=[ln(1+xy)]y=0y=1=ln(1+x)soJ=01ln(1+x)1+x2dxfromanothersideJ=01(01x(1+x2)(1+xy)dx)dyletdecomposeF(x)=x(1+x2)(1+xy)=α1+xy+ax+b1+x2α=limx1y(1+xy)F(x)=1y(1+1y2)=1y+1y=y1+y2limx+xF(x)=0=αy+aa=αy=11+y2F(x)=y(1+y2)(1+xy)+11+y2x+b1+x2F(0)=0=y1+y2+bb=y1+y2andF(x)=y(1+y2)(1+xy)+11+y2(x+y1+x2)01F(x)dx=11+y201ydx1+xy+12(1+y2)012x1+x2dx+y1+y201dx1+x2=11+y2[ln(1+xy)]x=0x=1+12(1+y2)[ln(1+x2)]01+π4y1+y2ln(1+y)1+y2+ln22(1+y2)+πy4(1+y2)J=01ln(1+y)1+y2dy+ln2201dy1+y2+π8012ydy1+y22J=π8ln2+π8ln2=π4ln2J=π8ln2.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com